Bagaimana forgiveness anak korban perceraian?: Studi deskriptif fenomenologi - adhelia rachma; Devi Puspitasari; Rahma Kusumandari (INNER: Journal of Psychological Research, 2023)
Abstract Divorce is the breaking of a husband and wife's relationship in marital status so that the two of them are no longer domiciled as husband and wife. This condition results in the absence of living together in the household. This research focuses on the true meaning of forgiveness in early adulthood. This study used a qualitative method with a descriptive phenomenological research type (PFD). The number of subjects in this study was 2 people using data collection techniques, observation, and interviews. The data analysis technique used in this study uses the data analysis model of Miles and Huberman, namely data triangulation which consists of data collection, data reduction, data presentation, and drawing conclusions. Children who are undergoing a divorce from their parents in Tambak Rejo Village have different mentalities so the process of expressing emotions is also not the same. Keywords: Forgiveness, divorce